Influence of the anti‐inflammatory cytokine interleukin‐4 on human joint capsule myofibroblasts. Issue 6 (21st August 2016) - Mattyasovszky, Stefan G.; Mausbach, Stefan; Ritz, Ulrike; Langendorf, Eva; Wollstädter, Jochen; Baranowski, Andreas; Drees, Phillipp; Rommens, Pol Maria; Hofmann, Alexander
ABSTRACT: Post‐traumatic joint contracture was reported to be associated with elevated numbers of contractile myofibroblasts (MFs) in the healing capsule. During the physiological healing process, the number of MFs declines; however, in fibroconnective disorders, MFs persist. The manifold interaction of the cytokines regulating the appearance and persistence of MFs in the pathogenesis of joint contracture remains to be elucidated. The objective of our current study was to analyze the impact of the anti‐inflammatory cytokine interleukin (IL)‐4 on functional behavior of MFs. Cells were isolated from human joint capsule specimens and challenged with three different concentrations of IL‐4 with or without its neutralizing antibody. MF viability, contractile properties, and the gene expression of both alpha‐smooth muscle actin (α‐SMA) and collagen type I were examined. Immunofluorescence staining revealed the presence of IL‐4 receptor (R)‐alpha (α) on the membrane of cultured MFs. The cytokine IL‐4 promoted MF viability and enhanced MF modulated contraction of collagen gels. Moreover, IL‐4 intervened in gene expression by up‐regulation of α‐SMA and collagen type I mRNA. These effects could be specifically lowered by the neutralizing IL‐4 antibody. On the basis of our findings we conclude that the anti‐inflammatory cytokine IL‐4 specifically regulates viability and the contractile properties of MFs via up‐regulating the gene expression of α‐SMA and collagen type I. IL‐4 may be a helpful target in developing anti‐fibrotic therapeutics for post‐traumatic joint contracture in human. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1290–1298, 2017. Abstract : Immunofluorescence staining revealed the presence of interleukin (IL)‐4 receptor (R)‐alpha (α) on the membrane of cultured myofibroblasts (MFs). IL‐4 promoted MF viability and enhanced MF modulated contraction of collagen gels by up‐regulation of alpha‐smooth muscle actin (α‐SMA) and collagen type I mRNA. These effects could be specifically lowered by the neutralizing IL‐4 antibody. IL‐4 may be a helpful target in developing anti‐fibrotic therapeutics for post‐traumatic joint contracture in human.